Variation in Viral Shedding Patterns between Domestic and Wild Terrestrial Birds Infected Experimentally with Reassortant Avian Influenza Virus (H9N2). (September 2016) - Umar, Sajid; Asif, Sajjad; Usman, Muhammad; Atif, Muhammad; Ali, Shahzad; Munir, Muhammad Tanveer; Ali, Asif; Shahzad, Muhammad; Shah, Muhammad Ali Abdullah
Avian influenza (H9N2) virus infection is an emerging respiratory problem and its prevalence varies significantly among different species of birds. The current knowledge about virus shedding parameters in terrestrial birds is limited. With this in mind, the present study was conducted in different domestic and wild terrestrial birds to investigate species-related differences in infectivity and pattern of viral shedding associated with H9N2 AI virus. Groups of terrestrial birds (domestic Guinea Fowl Numida meleagridis, Japanese Quail Coturnix coturnix japonica, House Sparrows Passer domesticus, House Crows Corvus splendens and Bank Myna Acridotheres ginginianus ) were inoculated intra-nasally with A/chicken/Pakistan/10RS3039-284-48/2010 (H9N2) AI virus (10 6 EID50 ) and then examined for infectivity and virus shedding patterns. With the exception of House Crows, all infected birds showed clinical signs of different severity, showing the most prominent disease signs in Japanese Quail. All infected birds showed positive results for virus shedding, however, the pattern of virus shedding was different among wild terrestrial birds. Japanese Quail showed the highest levels of virus shedding while samples collected from House Crows revealed only very low levels. Interestingly, virus shedding was observed predominantly via the gastrointestinal tract in House Sparrows and Bank Myna and via the buccal cavity route in Guinea Fowl and Japanese Quail. Here we investigated that the novel genotype of H9N2 AI virus circulating in Pakistan causes clinical disease signs in domestic and wild terrestrial birds. The results of this study suggest that virus shedding varies between different related avian species and highlights the potential role of Guinea Fowl, Japanese Quail, House Sparrows and Bank Myna as mixing bowls for the transmission and maintenance of H9N2 AI viruses between premises.